Dynamic distribution of gut microbiota during embryonic development in chicken - Fisayo T. Akinyemi (Poultry Science, 2020)
The gut microbiota is a complex ecological community and widely recognized in many aspects of research, but little is known on the relation between gut microbiota and embryonic development in chickens. The aim of this study was to explore the dynamic distribution of gut microbiota in chickens' embryos during stages of developments (chicken embryos that had incubated until day 3 [E3], day 12 [E12], and day 19 [E19]). Here, 16S rRNA gene sequencing was performed on the gut microbiota in chicken embryos across different developmental stages. Twenty-one phyla and 601 genera were present in chicken embryos, and 96 genera such as Ochrobactrum, Phyllobacterium, and Amycolatopsis were the core microbiota in the 3 stages of development. Second, 94 genera of microbes were found to change significantly between E3 and E12, and 143 genera significantly differed between E12 and E19 in chicken embryos (P < 0.05). Ochrobactrum and Amycolatopsis decreased with growth changes: E3 (30.4%), E12 (25.1%), and E19 (13.6%) and E3 (11.5%), E12 (7.4%), and E19 (5.6%), respectively. Contrarily, Phyllobacterium increased to 47.9% at E19, indicating the growing trend of microbial diversity among the embryos' development. Moreover, the principal component analysis showed a high level of similarities between E3 and E12 compared with E19, whereas the alpha analysis showed more diversity of gut microbiota at E19. Furthermore, the functional predictions showed that metabolic pathways such as energy metabolism and genetic information processing were significantly enriched on day 3 and day 12 in our study, suggesting their strong influence on growth, development, and immunity of chicken embryos. Our findings provide insights into the understanding of dynamic shifts of gut microbiota during chicken embryonic growth.